2003
DOI: 10.1034/j.1600-0722.2003.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of matrix metalloproteinases (MMPs) and tissue inhibitors of MMPs in mature human odontoblasts and pulp tissue

Abstract: Previous studies have demonstrated that (at least) matrix metalloproteinase (MMP)-2, -8, -9, -14 and -20 are expressed by human odontoblasts. Here, we analysed the expression of 19 MMPs and their specific tissue inhibitors (TIMP)-1, -2 and -3) -1, -2 and -3 in mature human odontoblasts and pulp tissue. Since MMP-20 is almost exclusively expressed by the dentin-pulp complex cells, we further analysed the effect of transforming growth factor (TGF)-beta1 and bone morphogenetic protein (BMPs)-2 on its expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
133
1
31

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(170 citation statements)
references
References 65 publications
(101 reference statements)
5
133
1
31
Order By: Relevance
“…In terms of protein expression, the variety of these proteases in the dentin-pulp complex has been claimed to be comparable with that described for MMPs (Palosaari et al 2003;Tersariol et al 2010;Tjäderhane et al 2013a). Similar to MMPs, cathepsins also participate in ECM degradation in physiological and pathological processes (Fig.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…In terms of protein expression, the variety of these proteases in the dentin-pulp complex has been claimed to be comparable with that described for MMPs (Palosaari et al 2003;Tersariol et al 2010;Tjäderhane et al 2013a). Similar to MMPs, cathepsins also participate in ECM degradation in physiological and pathological processes (Fig.…”
mentioning
confidence: 74%
“…The MMPs present in dentin are produced by odontoblasts (Palosaari et al 2003) during secretion of dentin matrix and are suggested to be involved in dentin formation. After mineralization of the collagen matrix, the inactive proforms of MMPs remain trapped within the calcified matrix (Hannas et al 2007), where they can be re-exposed and potentially activated during the dentin caries process.…”
Section: Dental Caries and Role Of Mmps In Caries Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been suggested that high levels of zymogens in the conditioned culture media indicates a lack of appropriate enzyme activators (37). MT1-MMP is a well known proMMP-2 enzyme activator (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Esses estímulos são promovidos pelas bactérias e seus produtos presentes no canal radicular e periápice e que acionam os mecanismos de defesa do hospedeiro (TORABINEJAD; KETTERING, 1985, BARKHORDAR;SOUZA, 1988). As células epiteliais em proliferação invadem a estrutura do granuloma periapical, aumentando, progressivamente, a massa de tecido epitelial e formando, concomitantemente, a microcavitação cística, cujo mecanismo está fundamentado em diversas teorias (MÁRTON; KISS, 2000, PALOSSAARI et al, 2003. As condições indutoras para provocar a proliferação epitelial dependem da diminuição da tensão de oxigênio, aumento da tensão de gás carbônico, associados a uma redução do pH.…”
Section: Cistos Periapicaisunclassified